Pengabdian kepada Masyarakat melalui Pelayanan Kesehatan dan Bantuan Kemanusiaan pada Korban Bencana Banjir di Kabupaten Aceh Tamiang 2026 - Zulkarnaini Zulkarnaini; Sri jumiati; Miftahul Rauzah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Flooding is a hydrometeorological disaster that frequently occurs in Indonesia and impacts the health and social life of the community. Aceh Tamiang Regency is an area with a high vulnerability to flooding, requiring handling through health services and humanitarian assistance. This community service activity aims to provide basic health services, health education, and humanitarian assistance to flood-affected communities in Aceh Tamiang Regency. The method used was descriptive with a participatory approach. The activity was carried out from March 3–10, 2026, targeting flood-affected communities, especially vulnerable groups. Health services included health checks, consultations, education, and medication administration as indicated, while humanitarian assistance in the form of basic necessities was distributed through coordination with local governments, village officials, health workers, and volunteers. The results of the activity showed a positive community response. The most common health complaints found included acute respiratory infections (ARI), skin disorders, fatigue, muscle and joint pain, and hypertension. The distribution of aid was on target and accompanied by education on post-flood disease prevention, the implementation of clean and healthy living behaviors (PHBS), and disaster preparedness. This activity contributes to meeting the community's basic needs, improving access to health services, and supporting accelerated post-disaster community recovery.Keywords: Flood, Health Services, Humanitarian Assistance, Community Service, Post-Disaster.